Effects of tourism promotion on COVID-19 spread: The case of the "Go To Travel" campaign in Japan. (September 2022) - Tamura, M.; Suzuki, S.; Yamaguchi, Y.
Abstract: Introduction: On July 22, 2020, the Japanese government launched the "Go to Travel" campaign that subsidizes 50% of personal travel expenditure to support the tourism industry under the COVID-19 pandemic. This policy was controversial from the viewpoint of infection spread and was temporarily cancelled in December 2020, though there was no statistical evidence. Methods: This is the first study that measures the extent to which this campaign increased COVID-19 cases. This study regards the campaign as a natural experiment: although Tokyo and its commuting areas experienced the same time-series trends of COVID-19 cases before the "Go To Travel" campaign, this campaign was implemented in areas outside Tokyo, but not in Tokyo. Then, the comparison (difference-in-differences) yields the campaign's effect. Results: The estimation shows that the "Go To Travel" campaign significantly raised the increment rate of cases by 23.7%–34.4% during July 30—August 4. There is no significant effect after August 5. In addition, our simulation identified the number of campaign-related cases in each city. Conclusions: Although the campaign significantly spread COVID-19, the effect was not continuous to permanently change the time-series trend. Highlights: This paper measures the extent to which the Japanese government's tourism campaign increased COVID-19 cases. The campaign (launched on July 22, 2020) raised the increment rate of cases by 23.7%–34.4% during July 30—August 4. The effect was not continuous to permanently change the time-series trend. Our simulation identified the number of campaign-related cases in each city.